Magnetic Chitosan Nanocomposites: A Useful Recyclable Tool for Heavy Metal Ion Removal - Liu, Xiaowang; Hu, Qiyan; Fang, Zhen; Zhang, Xiaojun; Zhang, Beibei (Langmuir, 2009)
Magnetic chitosan nanocomposites have been synthesized on the basis of amine-functionalized magnetite nanoparticles. These nanocomposites can be removed conveniently from water with the help of an external magnet because of their exceptional properties. The nanocomposites were applied to remove heavy metal ions from water because chitosan that is inactive on the surface of the magnetic nanoparticles is coordinated with them. The interaction between chitosan and heavy metal ions is reversible, which means that those ions can be removed from chitosan in weak acidic deionized water with the assistance of ultrasound radiation. On the basis of the reasons referred to above, synthesized magnetic chitosan nanocomposites were used as a useful recyclable tool for heavy metal ion removal. This work provides a potential platform for developing a unique route for heavy metal ion removal from wastewater.